2023
DOI: 10.3390/s23115184
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of In-the-Wild Datasets for Multimodal Emotion Recognition

Abstract: Multimodal emotion recognition implies the use of different resources and techniques for identifying and recognizing human emotions. A variety of data sources such as faces, speeches, voices, texts and others have to be processed simultaneously for this recognition task. However, most of the techniques, which are based mainly on Deep Learning, are trained using datasets designed and built in controlled conditions, making their applicability in real contexts with real conditions more difficult. For this reason,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…In another study, Li et al, explored the use of multimodal approaches for FER by integrating both facial and physiological signals [50]. Their work demonstrated that combining facial features extracted from deep convolutional neural networks with physiological signals, such as heart rate and electrodermal activity, resulted in enhanced emotion recognition accuracy.…”
Section: An Analysis Of Prior Research In the Relevant Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Li et al, explored the use of multimodal approaches for FER by integrating both facial and physiological signals [50]. Their work demonstrated that combining facial features extracted from deep convolutional neural networks with physiological signals, such as heart rate and electrodermal activity, resulted in enhanced emotion recognition accuracy.…”
Section: An Analysis Of Prior Research In the Relevant Fieldmentioning
confidence: 99%
“…Aguilera et al, [50] achieved an accuracy of 63.85% on the Emotion Recognition in the Wild dataset using a transfer learning approach with a pre-trained deep neural network. This was higher than the accuracy achieved by several other approaches.…”
Section: Performance Evaluation Of Transfer Learning For Facial Expre...mentioning
confidence: 99%